Tinjauan Maslahat dan Illat Hukum Pada Praktik Penyewaan Lahan Untuk Peternakan Babi di Kecamatan Sidamanik dalam Analisis Kaidah Hukum Asal Kebolehan Bermuamalah - Muhammad Sya’ban Siregar; Mhd. Syahnan; Fauziah Lubis; Dhiauddin Dhiauddin; Nisful Khoiri (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2025)
Leasing is a permissible contract in Islam. However, if the purpose of the lease transaction creates significant dynamics for Islam, research is necessary to determine its legal basis in Islam. This research was conducted in Sidamanik District, Simalungun Regency, where a Muslim, having been unable to find a tenant for his land for a long time, immediately rented it to someone with the intention of establishing a pig farm on the leased land, despite the exorbitant rental price. This led to environmental pollution and health problems for local residents. This research was conducted to determine the actions of Muslim landowners, analyzing the principles of the Lafadz (words of Islamic law) in transactions, specifically regarding the practice of leasing land for pig farming. In the context of Islamic law, the basic principle of the permissibility of muamalah (economic transactions) is exempted when it comes to activities involving prohibited objects, such as pigs. This study aims to analyze the Islamic legal perspective on land leasing for pig farming and its implications for business actors. The research method used is descriptive analysis with a qualitative approach through a literature review of Islamic legal sources, including the Quran, Hadith, and the opinions of scholars. The results indicate that the practice of land leasing for pig farming has generated differing opinions among scholars, with the majority deeming it prohibited based on the prohibition of pork in Islam. This research is expected to contribute to the development of a deeper understanding of muamalah law and its application in the contemporary context, as well as provide guidance for Muslims in conducting economic activities in accordance with Islamic law